Involvement of the Mannose Phosphotransferase System of Lactobacillus plantarum WCFS1 in Peroxide Stress Tolerance - Stevens, Marc J. A. (American Society for Microbiology (ASM), 2010)
A Lactobacillus plantarum strain with a deletion in the gene rpoN, encoding the alternative sigma factor 54 (σ(54)), displayed a 100-fold-higher sensitivity to peroxide than its parental strain. This feature could be due to σ(54)-dependent regulation of genes involved in the peroxide stress response. However, transcriptome analyses of the wild type and the mutant strain during peroxide exposure did not support such a role for σ(54). Subsequent experiments revealed that the impaired expression of the mannose phosphotransferase system (PTS) operon in the rpoN mutant caused the observed increased peroxide sensitivity.